Acute Mesenteric Ischemia, Atypical Presentation as Acute Appendicitis in Two Young Patients: Case Report - Nava-Coronado, A; Rodríguez-Díaz, J. G.; Vite-Pineda, K. Y.; Medina-Martínez, A.; González-Soto, J. R.; Falcón-Cancino, Luis Arturo; Padrón-Arredondo, G. (British Journal of Healthcare and Medical Research, 2023)
Introduction: Mesenteric ischemia occurs when visceral tissues receive an inadequate supply of blood supply. This can result from arterial thrombus, arterial embolus, venous thrombosis limiting arterial flow, and extrinsic compression of the blood vessels. Clinical Cases: Case 1: A 27-year-old female with a clinical picture of burning pain of 10 out of 10 intensity in the lower abdomen that radiates to the navel and right iliac fossa, accompanied by headache, diarrhea and vomiting for six days prior to admission, fever of 38 °C. He has a torpid evolution in his post-surgery with progression to multiple organ failure 3 days after surgery, beginning with hemodynamic failure with a requirement for vasoactive amines, in addition to bleeding from a nasogastric and transvaginal tube, severe thrombocytopenia. Intubation was decided due to acute respiratory failure Heart rate of 160 x', increased respiratory pattern RF of 45x'. She died three days later, due to multiple organ failure. Case 2: A 32-year-old female with Polycystic Ovary Syndrome diagnosed at 13 years of age under treatment for the first 3 years with discontinued hormonal contraceptives. Due to risk and age, admission to the intensive care unit was decided, where 3 days later the oral route was started, with adequate tolerance with liquids, for which it was decided to go to the floor in charge of our service. The patient is stable. Conclusions: Acute mesenteric ischemia is a rare pathology, but due to its high morbidity and mortality it requires extensive knowledge about its risk factors, symptoms, diagnosis and treatment, since timely recognition leads to a satisfactory evolution. In this type of young patients with no recognized risk factors, diffuse abdominal pain and imaging and imaging studies with non-specific findings make it necessary to rule out the most frequent abdominal pathologies and suspect them.